Artificial Intelligence In Project-Based Learning as a Resource for Learning Local History In Bandung - Kusmarni, Yani; Santosa, Ayi Budi; Winarti, Murdiyah; Kurniawati, Yeni; Yulianti, Iing; Gumelar, Faujian Esa; Pangestu, Dimas Aldi (Diakronika, 2024)
The history learning process today needs to optimize the use of technology. Optimizing technology, especially artificial intelligence, can avoid the negative effects of students' use of gadgets. Project Based Learning is a model that AI can integrate into history learning. This article outlines the Project Based Learning (PjBL) model that utilizes Artificial Intelligence (AI) as an ICT platform in the Local History curriculum. The research methodology is descriptive and qualitative, involving data collection methods such as observation, interviews, and documentation. The project focuses on historic buildings that reflect Bandung’s history, architecture, and culture, particularly Gedong Tjai Tjibadak. The study results show that 1) the PjBL model effectively combines with Artificial Intelligence (AI). 2) Presenting Local History content in a different format makes the learning experience more diverse and exciting. And 3) Utilizing AI-based projects as educational tools for history allows students to demonstrate their abilities effectively. The AI-integrated PjBL model enhances the learning of Local History content in a way that meets the requirements. AI technology makes learning smoother, more convenient, and more captivating.